Significance of Oxirane Rings in Epoxidized Palm Oil and Effects on the Coating Performance: Comparison between Epoxidized Unripe Palm Oil and Epoxidized Used Cooking Oil towards Adhesion Performance - Nurul Hazirah Aina Hasnan; Najmiddin Yaakob; Muhammad Nadzmi Abu Kassim; Umie Amira Mohd Noh (Universitas Gadjah Mada, 2020)
In this study, epoxy coatings made up from petroleum-based epoxy resin mixed with two different types of palm oils were prepared and compared. The commercial epoxy resin based on diglycidyl ether of bisphenol A (DGEBA) were formulated with epoxidized unripe palm oil (EPO) and another one with epoxidized used cooking oil (ECO) at four different ratios (0:100, 10:90, 20:80 and 30:70). The EPO and ECO were prepared through generated in situ of performic acid (HCOOH) and hydrogen peroxide (H2O2) by a fixed molar ratio of 1:5:4 mol/mol (EPO/ECO: HCOOH:H2O2). The reaction took place at constant temperature (45 °C) with continuous stirring for 150 min to obtain 95.5% oxirane conversion with 90.0% yield. The EPO and ECO were characterized by using Fourier Transform Infrared (FTIR) spectroscopy analysis. X-Cut and Cross-Cut methods were used in the test performance of adhesion strength. The results obtained from adhesion test for EPO were good as the coatings only experienced small trace of peeling. On the other hand, only minimal performances were obtained from the ECO coated metal. This was due to the presence of oxirane in EPO as compared to that of in ECO. EPO has a potential to replace petroleum-based resin in epoxy coating formulation according to its remarkable performances.